"Croatian American Diasporic Literature?" - Šesnić, Jelena (2006)
The presentation deals with some conceptualizations of the term diaspora as it is applied in cultural and ethnic studies nowadays, and shows how these can be applied with some adjustments to a reading of Vladimir Goss's work _Antigonin dnevnik_ (Antigone's Diary, 1993), as an instance of an emergent Croatian American diasporic writing.
Projekt MZOS
ENG